2013
DOI: 10.1017/s0031182013000826
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial drug discovery – the path towards eradication

Abstract: SUMMARYMalaria is a disease that still affects a significant proportion of the global human population. Whilst advances have been made in lowering the numbers of cases and deaths, it is clear that a strategy based solely on disease control year on year, without reducing transmission and ultimately eradicating the parasite, is unsustainable. This article highlights the current mainstay treatments alongside a selection of emerging new clinical molecules from the portfolio of Medicines for Malaria Venture (MMV) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
102
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 46 publications
0
102
0
1
Order By: Relevance
“…The renewed resources and efforts in the last decade for malaria eradication have contributed to a significant expansion of the antimalarial drug portfolio (42). To promote the eradication of malaria, the Malaria Eradication Research Agenda initiative suggested that drug development efforts should concentrate on Single Encounter Radical Cure and Prophylaxis (SERCaP), which encompasses drugs with multistage activities (including liver and transmission-blocking activity), relapse prevention, and long-lasting effects to provide prophylactic treatment (43,44). Recent projects aiming to identify novel chemical scaffolds for malaria drug discovery have relied on high-throughput screening strategies (42), which focus on phenotypic-and target-based screens.…”
Section: Challenges and Current State Of Malaria Drug Developmentmentioning
confidence: 99%
“…The renewed resources and efforts in the last decade for malaria eradication have contributed to a significant expansion of the antimalarial drug portfolio (42). To promote the eradication of malaria, the Malaria Eradication Research Agenda initiative suggested that drug development efforts should concentrate on Single Encounter Radical Cure and Prophylaxis (SERCaP), which encompasses drugs with multistage activities (including liver and transmission-blocking activity), relapse prevention, and long-lasting effects to provide prophylactic treatment (43,44). Recent projects aiming to identify novel chemical scaffolds for malaria drug discovery have relied on high-throughput screening strategies (42), which focus on phenotypic-and target-based screens.…”
Section: Challenges and Current State Of Malaria Drug Developmentmentioning
confidence: 99%
“…Even for artemisinins, which until now were safe and effective, resistance is a growing issue in Asia, particularly on the Cambodia-Thailand border, which is the cradle of antimalarial resistance (3,4). New drugs and new lead compounds for antimalarial drug development are greatly needed (5).…”
mentioning
confidence: 99%
“…The Medicines for Malaria Venture (MMV) has defined four target candidate profiles (TCPs) that describe the requirements for novel tools for the control and elimination of malaria (6). In particular, new multistage antimalarial drugs able to kill the liver or sexual stages of the parasite and/or that are capable of preventing the parasite development in the mosquito are needed (5,6). Gametocytes are the sexual stage of Plasmodium, which appear concomitantly in the circulation or after the asexual intraerythrocytic stage.…”
mentioning
confidence: 99%
“…The intensification of the studies related to natural substances to combat malaria resulted in many herbal extracts which have been tested to verify the antiplasmodial activity, but only a limited number of active compounds, belonging to different molecular classes, were isolated and identified (Burrows et al, 2013).…”
Section: Introductionmentioning
confidence: 99%